Food practices in transition changing food consumption, retail and production in the age of reflexive modernity - Spaargaren, Gert.; Oosterveer, Peter; Loeber, Anne. (New York : Routledge, 2012)
"This edited volume presents and reflects upon empirical evidence of "sustainability"-induced and -related transition in food practices. The material collected in the various chapters contributes to our understanding of the ways in which ideas and preferences, sociotechnological developments and changes in the governance of food interact and become visible in practices of consumption, retail and production."--
pt. 1. Transitions in consumer practices -- pt. 2. Transitions in retail -- pt. 3. Transitions in production practices.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Food industry and trade; Food industry and trade -- Environmental aspects; Food consumption; Agricultural ecology; Electronic books